Torsional Behavior of High-Strength Concrete Beams with Minimum Reinforcement Ratio - Changbin Joh; Imjong Kwahk; Jungwoo Lee; In-Hwan Yang; Byung-Suk Kim (Advances in Civil Engineering)
Although there is a growing trend to use higher strength for concrete and steel in reinforced concrete structures due to the lightness and slenderness of these members together with the simplified arrangement of their reinforcement, there is still the necessity to inspect the reduction of ductility resulting from the gain in strength. Taking into account that this also concerns the design for torsion, this study intends to investigate the regulations related to the torsional minimum reinforcement ratio in view of the minimum ductility requirement with focus on Eurocode 2. To that goal, the relation between the torsional cracking moment and the ductile behavior is discussed for the beam reinforced with the minimum torsional reinforcement ratio to examine the eventual properness of the minimum torsional reinforcement ratio recommended by Eurocode 2. Moreover, a pure torsion test is performed on 18 beams made of 80 MPa concrete reinforced by high-strength bars with rectangular section and various test variables involving the minimum torsional reinforcement ratio, the transverse-to-longitudinal reinforcement ratio, and the total reinforcement ratio. As a result, for the high-strength concrete beams, the minimum torsional reinforcement ratio recommended by Eurocode 2 was insufficient to prevent the sudden loss of strength after the initiation of the torsional cracking. But with regard to the compatibility torsion of statically indeterminate structure, the adoption of the minimum torsional reinforcement ratio recommended by Eurocode 2 might secure enough deformability under displacement-controlled mode to allow the redistribution of the torsional moment.